Timber harvesting, non timber forest products and rural livelihoods in Central Africa - Ndoye, O. (International Union for Conservation of Nature, 2003)
Many trees are important to local communities for health, income, nutrition, and construction purposes, and to timber companies for their wood. Timber production and exports have increased in Central Africa over the last decade. Furthermore, the number of species exploited for timber purposes have also increased since the devaluation of the CFA Francs. All these factors have negative impact on forest resources and on biodiversity. Trees harvested for their timber take many years to mature. The destruction of these resources is a threat to rural livelihood. The paper argues that a balanced approach is needed to take into account both the interests of rural communities and timber companies. This will require, among others, the respect by timber companies of the management plans they draw, the exclusion from harvesting of selected timber species that are important to local communities, and the need to involve rural communities in the monitoring of the activities of timber companies.